LANGUAGE LEARNING STRATEGIES USED BY ENGLISH PREPARATORY SCHOOL OF EFL LEARNERS IN THE UNIVERSITIES OF CYPRUS - Rahat Bashir; Nohaiz Mehmood; Sana Khan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The study aims to discuss the language learning strategies (LLS), which EFL learners employ during the learning process in the classrooms ofCyprus. As language learning continues to develop, linguistic innovations keep evolving. There are several factors, including motivation, kind of ability, language habits, and gender, that influence the learning strategies. In this study, Cyprus International University EFL students’ application of language learning strategies in Cyprus is analyzed, and a mixed-method research technique is employed. The participants included 250 Cyprus International UniversityPreparatory school students. The questionnaire demonstrating different language learning strategies is used for the collection of data. Mixed techniques for information compilation have been used in present studies. A similar technique was used with the input of Oxford’s Strategy Inventory for Language Learning (1990) to define variations in LLS usage and its modifications. For determining the connection between these variables and LLS, the survey information was assessed by utilizing SPSS as a statistical tool. In order to explain their behavior on language education policies, a half-structured debate with two active communities was used. According to the research results, there is a significant connection between the use of language learning strategies with gender and language proficiency. However, it is not so with age. The findings also indicated that memory, cognition, and social strategies all have a positive correlation with the EFL learners’ language learning strategies. However, metacognitive, affective, and compensation strategies tend to have an adverse effect.